Highly efficient removal of heavy metal ions from polluted water using ion-selective polyacrylonitrile nanofibers. Issue 1 (February 2018) - Morillo Martín, D.; Faccini, M.; García, M.A.; Amantia, D.
Graphical abstract: Highlights: Ion-selective nanofibers were developed by electrospinning and chemical grafting. Nanofibrous adsorbents are extremely effective to remove heavy metals from water. The selectivity in presence of interfering metals ions and anions was assessed. Nanofibers can be regenerated and reused for several cycles. Removal of >99% of metal ions was achieved operating in continuous flow. Abstract: Nanostructured materials have been successfully applied to efficiently remove toxic and carcinogenic contaminants such as heavy metals from wastewater. In this work, polyacrylonitrile (PAN) was selected as base polymer for electrospinning process to obtain easily modifiable and versatile nanofibers able to remove selectively heavy metal ions from contaminated effluents. Chemical functionalities were grafted in a stable and homogeneous way by a two steps grafting process which involves hydrolysis and chemical modification with ethylenediamine (EDA), ethyleneglycol (EG) or diethylenetriamine (DTA) resulting in three ion-selective nanofibrous materials. Their adsorption behaviour was tested against Cu(II), Pb(II) and Zn(II) reaching extremely high adsorption capacities of 6.1 mmol/g, 8.8 mmol/g and 7.2 mmol/g, respectively.